Therapeutic Efficacy of Thymoquinone in Attenuating Obstructive Renal Fibrosis: A Dose-Response Analysis of Tumor Necrosis Factor-Alpha Suppression and Histopathological Remodeling - Edy Nur Rachman; Suprapti; Muhammad Irsan Saleh; Ian Effendi; Zulkhair Ali; Novadian (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Chronic kidney disease is characterized by progressive renal fibrosis, a maladaptive process driven by chronic inflammation and extracellular matrix accumulation. Tumor necrosis factor-alpha (TNF-α) plays a central role in this fibrogenic cascade. Thymoquinone (TQ), the primary bioactive compound of Nigella sativa, exhibits potent anti-inflammatory properties. Methods: In this therapeutic intervention model, 107 male Wistar rats were subjected to Unilateral Ureteral Obstruction (UUO). To test TQ's ability to halt established fibrogenesis, treatment was delayed until day 7 post-obstruction. Rats were randomized to receive TQ intraperitoneally at 5, 10, or 20 mg/kg body weight for 14 days. Outcomes included renal function (urea/creatinine), tubulointerstitial injury (PAS staining), fibrosis area (Sirius Red staining), and localized TNF-α mRNA expression (reverse transcriptase PCR normalized to GAPDH). Data were analyzed using ANOVA followed by Tukey’s Honestly Significant Difference (HSD) test. Results: UUO induced significant structural injury and upregulated TNF-α expression compared to sham controls (p < 0.001). TQ intervention significantly reduced the tubulointerstitial injury score, with the greatest reduction at 20 mg/kg (p < 0.01). The positively stained fibrotic area exhibited a U-shaped response, maximally decreased at the 10 mg/kg dose (p < 0.01). Similarly, TNF-α mRNA relative expression was significantly suppressed by TQ, exhibiting a pharmacological ceiling effect at 10 mg/kg (p < 0.01). Conclusion: Thymoquinone administered therapeutically mitigates established structural renal fibrosis and tubulointerstitial injury by downregulating TNF-α-mediated inflammation. A 10 mg/kg dose represents the optimal therapeutic threshold for anti-fibrotic efficacy in obstructive nephropathy.